Estudio sobre la orientacion de surcos en la siembra de frijol en los municipios de San Gil y Villanueva (Santander) - Maître, Adrian (International Center for Tropical Agriculture, 1991)
Thirty bean lots, belonging to 28 farmers, were monitored in the municipalities of San Gil and Villanueva. Short interviews were conducted with the farmers to determine why they use certain types of furrows and their perception of erosion processes. Lots were divided into 3 groups: furrows down the slope, furrows across the slope, and inclined furrows. Results indicated that farmers who plant across the slope or with inclined furrows try to avoid or reduce soil erosion, leaching of fertilizers, and crop damage, and manage soil moisture. Those farmers planting down the slope try to make cultural practices easier. There was no significant difference among the groups of farmers as to the perception of erosion. Most consider that frequent plowing adversely affects the soil, but deem it necessary before each sowing. Sustainable crop management of recently cleared land is uncommon among farmers in the region. (CIAT)